If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2 + 5i) + (-1 + 5i) = 0 Remove parenthesis around (2 + 5i) 2 + 5i + (-1 + 5i) = 0 Remove parenthesis around (-1 + 5i) 2 + 5i + -1 + 5i = 0 Reorder the terms: 2 + -1 + 5i + 5i = 0 Combine like terms: 2 + -1 = 1 1 + 5i + 5i = 0 Combine like terms: 5i + 5i = 10i 1 + 10i = 0 Solving 1 + 10i = 0 Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 10i = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 10i = 0 + -1 10i = 0 + -1 Combine like terms: 0 + -1 = -1 10i = -1 Divide each side by '10'. i = -0.1 Simplifying i = -0.1
| b/12-100=25 | | x/-3=11 | | 6x-1=5x-6 | | 9t-10=17-9t | | 5+w/8=30 | | 4r+5s-16r+3s= | | 32+4t-t=40 | | 1/2+t-2=-3/2 | | 6q-12=35 | | 0=t+[-14] | | 3.3=40w | | x/3e | | 3x^2+44x+96=0 | | y-60=-8.50(x-20) | | 24=m+37 | | -4x+3(2x+12)=18 | | 6x+2y=-7 | | 2x+10/3+x-10/4=9/2 | | 3x^2+19x-154=0 | | 76=6x+2(4x+3) | | 1.2x+.3x=-6 | | 3w-2+2w=-18 | | (w+5)(w-7)= | | 4x-5=8x-2 | | 12(+3y)= | | 4x+18=3(x+3) | | X^2+4x+16=18.25 | | 9.07x+27.21=54.42 | | Log(8)1-5X=log(8)3x+7 | | -x=10-2x | | 29=x-56/2 | | -2(8-4x)=-19+8x |